Spatial evidence of cross-crop pesticide contamination in small-holder Thai farms - Dunn,R.A. (Springer Science + Business Media, 2015)
© 2013, INRA and Springer-Verlag France. Development efforts for the reduction of land use needs and the improvement of farmer livelihoods in northern Thailand have resulted in the introduction of new pesticide-intensive crop species. Cholinesterase-inhibiting pesticides pose a health risk to farmers and consumers, though pesticide exposure pathways are not well understood. Farmers believe that cross-crop pesticide contamination between ornamental chrysanthemums and food crops is a possible source of pesticide exposure. Therefore, we used spatial analysis to test the hypothesis that cross-crop pesticide contamination may be a pesticide exposure pathway. Data on cholinesterase inhibition detection on food crops from 2006 to 2008 were spatially correlated with crop field areas and chrysanthemum cultivation areas. Statistical analysis was used to determine factors that influence the likelihood of cholinesterase inhibition detection on a crop. Our results show that the application of cholinesterase-inhibiting pesticides to a food crop contributed significantly to the likelihood that the crop would exhibit cholinesterase inhibition, but accounted for less than 10 % of the total cases of detection. Demonstration of cross-crop pesticide contamination is given by greater detection for crops grown closer to chrysanthemum cultivation areas, crops tested on days of the week when samples were taken directly from the field based on proximity to chrysanthemum cultivation, and crops of species with more exposed edible parts. Mechanical barriers may be useful in reducing the risk of cross contamination.